FINANCIAL LITERACY INNOVATION FOR ENHANCING THE FINANCIAL CAPABILITIES OF MSME - Anggi Somba Poddala; Sonia Virginia Nawi; Yonas Ferdinand Riwu; Dyah Wahyu Nastiti (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2026)
This study aims to examine the influence of financial behavior, financial attitudes, and financial knowledge on the financial capabilities of MSMEs in Kupang City, as well as to understand the interaction of these three dimensions of financial literacy in improving MSME financial capabilities. The methodology used was a quantitative technique with an exploratory design. Data was collected through an online questionnaire distributed to 200 MSMEs in Kupang City, targeting only 173 MSMEs. Data were analyzed using SPSS 25. The results of this study indicate that financial behavior and attitudes have a significant influence on improving the financial capabilities of MSMEs in Kupang City. Financial knowledge has little impact if not balanced with supportive habits and attitudes. This study emphasizes the importance of a comprehensive financial literacy program to increase knowledge and improve financial behavior and attitudes of MSMEs in Kupang City in order to enhance their financial capabilities